Changes in Lung Diffusing Capacity of Elite Artistic Swimmers During Training - García, Iker; Drobnic, Franchek; Pons, Victoria; Viscor, Ginés (International Journal of Sports Medicine, 2020)
Artistic swimmers (AS) are exposed to repeated apnoeas in the aquatic environment during high intensity exercise provoking specific physiological responses to training, apnoea, and immersion. This study aimed to evaluate the changes in lung diffusing capacity in AS pre-, mid- and post-training in a combined session of apnoeic swimming, figures and choreography. Eleven elite female AS from the Spanish national team were the study’s participants. The single-breath method was used to measure lung diffusing capacity for carbon monoxide (DLCO) and one-way repeated measures ANOVA was utilized to evaluate the statistical analysis. Basal values of DLCO were higher than normal for their age and height (33.6±4.9 mL·min−1·mmHg−1; 139±19%) and there were a significant interaction between DLCO and AS training (ŋ2p=0.547). After the apnoeic swimming (mid-training) there was an increase in DLCO from basal to 36.7±7.3 mL·min−1·mmHg−1 (p=0.021), and after the figures and choreography (post-training) there was a decrease compared to mid-training (32.3±4.6 mL·min−1·mmHg−1, p=0.013). Lung diffusing capacity changes occur during AS training, including a large increase after apnoeic swimming. There were no differences in lung diffusing capacity from pre- to post-training, although large inter-individual variability was observed.
Keywords: diffusing capacity; lung diffusing capacity for carbon monoxide (DLCO); artistic swimming; synchronized swimming; swimming-induced pulmonary oedema (SIPO)